Upaya Penurunan In Line Scrap Pasting Process Melalui Penerapan Konsep Kaizen (Studi Kasus di Industri Automotive Baterry) - Darmawan, Heru; Wiyatno, Tri Ngudi (JURNAL TEKNIK INDUSTRI, 2020)
PT. XYZ is a manufacturing company that produces motorcycle and car batteries. In carrying out the battery manufacturing process, PT. XYZ really pays attention to the quality of the products it produces. The obstacles that are still faced at PT. XYZ, namely the still high scrap rate, which is 2.27%, with the dominant scrap being plate scrap, which is 84%, of which 55% comes from the pasting process with the plate scrap ratio reaching 2.45%, so that this problem can reduce productivity levels and increase production costs. Therefore, we need a method that can reduce the high number of defects so that the target plate scrap ratio of 1.39% set by the company can be achieved. One way that can be done is to identify and analyze the factors causing scrap by applying the kaizen concept to the PDCA stage. Kaizen is a way of continuous improvement that involves everyone, both managers and employees, to get optimal results. From the results of the application of Kaizen with stages of 8 PDCA steps, it can be seen that the scrap rate in 2016 was 1.35% or 0.04% lower than the target of 1.39%, whereas when compared to the scrap rate in 2015 which reached 2.45%, it means that the corrective steps have been taken. This was done in particular by reducing scrap plates due to the presence of scrap because jamming plates and plate drop which dominantly contributed to scrap plates in pasting, and this was able to reduce scrap plate by 55.1% in the pasting process and from this result many benefits were obtained by the company either directly or indirect.